Orthodontıc And Surgıcal Treatment Of Multıple Unerupted Teeth (Report Of A Cleidocranial Dysplasia Case ) - Neslihan Üçüncü (Galenos Yayinevi, 2000)
In this case report, a cleidocranial dyplasia case having failure of the teeth to erupt and multiple unerupted supernumerary teeth was introduced and orthodontic and surgical treatment was explained. This type of cases was only treated by prosthetic approach in the past. Recently, several treatment alternatives has been developed. However, the treatment of this type of cases is still difficult and requires long and interdisipliner work. This case report described unerupted permanent teeth, to move them into a satisfactory functional and aesthetic position with interdisciplinary management.